1990
DOI: 10.1080/00288233.1990.10430665
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the Duroc, Hampshire, Landrace, and Large White as terminal sire breeds of crossbred pigs slaughtered at 85 kg liveweight

Abstract: Anon-farrnstudywasundertaken,frrstly, to compare the Duroc and Hampshire as terminal sires in a three-way cross including the Landraceand Large White breeds and, secondly, to evaluate the latter cross against a two-way backcross involving the White breeds. Three boars of each sire breed were mated with crossbred sows of Large White, Landrace breeding and the progeny were grown to 85 kg liveweight on ad libitum feeding. Duroc-and Hampshire-sired litters hadrelatively fewer stillbirths but breed of sire did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Overall, the present findings coupled with those of the previous paper (Smith et al 1990) suggest that benefits in economy of production and carcass composition are likely to arise from using the Duroc and Hampshire breeds as terminal sires on whitecross dams compared with Landrace or Large White boars. The outcome regarding meat quality of the crosses is not so clear, particularly with respect to the condition of the muscle tissue in Hampshire crosses and the intramuscular fat level and its association with eating quality of the meat in Duroc crosses.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Overall, the present findings coupled with those of the previous paper (Smith et al 1990) suggest that benefits in economy of production and carcass composition are likely to arise from using the Duroc and Hampshire breeds as terminal sires on whitecross dams compared with Landrace or Large White boars. The outcome regarding meat quality of the crosses is not so clear, particularly with respect to the condition of the muscle tissue in Hampshire crosses and the intramuscular fat level and its association with eating quality of the meat in Duroc crosses.…”
Section: Discussionsupporting
confidence: 76%
“…Results from the first part of this study (Smith et al 1990), along with those of previous experiments conducted here ) and overseas (McGloughlin et al 1988) have shown that pigs sired by Duroc or Hampshire boars frequently grow faster, have higher carcass dressingout percentages, and produce carcasses with less fat and larger eye-muscle areas than those sired by Landrace or Large White boars. With Duroc crosses these superior performance characteristics have generally been accompanied by higher levels of intramuscular fat which are considered by some to be beneficial for eating quality (Barton-Gade 1987; Barton-Gade 1988;Martel et al 1988;Wood et al 1988;.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…The main characteristic of American Duroc is that it has a fast growth rate (Smith et al, 1990). In our studies the average body weight of Duroc is lower than the other two breeds from entrance to 100 days in the test station.…”
Section: Discussionmentioning
confidence: 82%